Pengaruh Penambahan Limbah Bottom Ash Terhadap Kuat Geser Pada Tanah - Eltrit Bima Fitrian; Demensi; Irwan Lie Keng Wong (Paulus Civil Engineering Journal, 2023)
The impact of adding bottom ash waste to a Direct Shear Test for clay soils with low shear strength and high compressibility is investigated in this study. The research entails evaluating the soil's physical properties and setting up bottom ash waste tests for the Direct Shear Test. For the first and second direct shear force tests, four test samples were utilized. The 15%, 20%, and 25% make up the utilized bottom ash waste mixture. The findings demonstrated that the soil possesses medium flexibility and inorganic clay's physical characteristics. In direct shear force testing, soil samples from points 1 and 2 yielded cohesion values (c) and shear angle values (). For point 1 soil samples, cohesiveness (c) values increased by 0.025 kg/cm2, 0.041 kg/cm2, 0.069 kg/cm2, and 0.076 kg/cm2, while shear angle (φ) values increased by 10.32°, 10.67°, 10.38°, and 14.16°. Additionally, cohesiveness (c) values of 0.048 kg/cm2, 0.077 kg/cm2, 0.084 kg/cm2, and 0.096 kg/cm2 and shear angle (φ) values of 11.82°, 14.35°, 14.20°, and 14.10° increased in Point 2 soil samples. According to the results, adding bottom ash waste increases the shear strength (c) and shear angle (φ) of the soil. It has been discovered that adding bottom ash waste to soil enhances its load-bearing capacity.